2020
DOI: 10.4094/chnr.2020.26.3.323
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Hope and Quality of Life among Adolescents with Chronic Diseases: A Systematic Review

Abstract: Purpose: Hope has been identified as a protective factor that contributes to achieving a better quality to life, especially in patients with chronic disease. The purpose of this review was to synthesize current knowledge about the relationship between hope and quality of life among adolescents living with chronic illnesses.Methods: We searched major English-language databases (PsycINFO, PubMed, and CINAHL) for studies from January 1, 2002 to July 12, 2019. Studies were included if they provided data on hope an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
(28 reference statements)
2
11
0
1
Order By: Relevance
“…Social function assessment describes a child's ability to interact with peers and get along with friends at school. Assessment of school functions describes a child's ability to do the tasks given at school (Kavitha & Padmaja, 2019;Mardhiyah et al, 2020;Nikmah & Mauliza, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social function assessment describes a child's ability to interact with peers and get along with friends at school. Assessment of school functions describes a child's ability to do the tasks given at school (Kavitha & Padmaja, 2019;Mardhiyah et al, 2020;Nikmah & Mauliza, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if the physical condition is considered stress, a substance resembling beta-carboline, a GABA antagonist, causes a decrease in the number (down-regulate) of GABA receptors. It then causes reduced resistance to anxiety and eases reactions to stress (Isworo et al, 2012;Kavitha & Padmaja, 2019;Mardhiyah et al, 2020). Emotional dysfunction is influenced by various things, such as feeling depressed during diagnosis, therapy that must be undertaken regularly every month and skipping school because of having to undergo therapy (Nikmah & Mauliza, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Becoming a PMC journal and being searchable in PubMed will trigger the recruitment of manuscripts from researchers worldwide, although CHNR's regional scope is currently mainly Korea. After becoming a Scopus-indexed and English-only journal, unsolicited submissions were received from countries outside Korea, including Indonesia, Egypt, and Nepal [2][3][4][5][6]. After being listed in PMC and PubMed, this trend will be accelerated since these two databases are very wellknown among nursing researchers.…”
Section: Chnrmentioning
confidence: 99%
“…The relationship between hope and quality of life in adolescents has been evaluated in various chronic diseases, across multiple countries, cultures, and settings. A systematic review of five included studies found a positive correlation between hope and quality of life; hope was found to have both direct and indirect effects on QOL in adolescents with chronic diseases [27]. Hope is considered as a protective role for improving the quality of life in adolescents with cancer [28].…”
Section: Introductionmentioning
confidence: 99%